2021
DOI: 10.48550/arxiv.2103.15913
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optical cycling of AlF molecules

Simon Hofsäss,
Maximilian Doppelbauer,
Sid Wright
et al.

Abstract: Aluminium monofluoride (AlF) is a promising candidate for laser cooling and trapping at high densities. We show efficient production of AlF in a bright, pulsed cryogenic buffer gas beam, and demonstrate rapid optical cycling on the Q rotational lines of the A 1 Π ↔ X 1 Σ + transition. We measure the brightness of the molecular beam to be > 10 12 molecules per steradian per pulse in a single rotational state and present a new method to determine its velocity distribution in a single shot. The photon scattering … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…Recently, we identified the aluminum monofluoride (AlF) molecule as a promising candidate for laser cooling. Its virtues include a large photon scattering rate and favorable Franck-Condon factors [57][58][59]. Moreover, we demonstrated that AlF molecules can be efficiently produced in a pulsed buffer-gas source, with a yield of > ∼ 10 12 molecules per steradian per pulse [58].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Recently, we identified the aluminum monofluoride (AlF) molecule as a promising candidate for laser cooling. Its virtues include a large photon scattering rate and favorable Franck-Condon factors [57][58][59]. Moreover, we demonstrated that AlF molecules can be efficiently produced in a pulsed buffer-gas source, with a yield of > ∼ 10 12 molecules per steradian per pulse [58].…”
Section: Introductionmentioning
confidence: 85%
“…Its virtues include a large photon scattering rate and favorable Franck-Condon factors [57][58][59]. Moreover, we demonstrated that AlF molecules can be efficiently produced in a pulsed buffer-gas source, with a yield of > ∼ 10 12 molecules per steradian per pulse [58]. A high yield of cryogenically thermalized molecules is a key prerequisite for reaching quantum degeneracy in a cooling step that follows upon laser cooling, namely forced evaporation.…”
Section: Introductionmentioning
confidence: 89%
“…We also expect them to be relevant for species with similar structure, like isotopologues of CaF, SrF or radioactive RaF [30] containing metal atoms with nonzero nuclear spin. Other examples where optical cycling and laser cooling of diatomic molecules with two nuclear spins have recently been considered include AlF [31], TlF [32] and YbOH [33], but detailed studies of laser cooling forces have so far been lacking. * t.langen@physik.uni-stuttgart.de Relevant energy levels for the laser cooling of 137 BaF including their relative energy shifts.…”
Section: Introductionmentioning
confidence: 99%